v.3; c.1 - "Kapila, Uma (ed.)" (Delhi, 1990)
53 Chapters in Three Volumes cover, among other issues, Objectives of Planned Economic Development and Role of the State; the Institutional Framework; Pattern of Asset Ownership in Agriculture & Industry; Demo graphic Constraints; Resources Constraints; Fiscal Policy for Financing Development; Structural Changes; Saving Behaviour, Inter State Disparities in Economic Development; Assessment of Growth Experience; Poverty, Unemployment and Economic Inequalities; Issues relating to Agriculture, Industry & Foreign Trade; Inter-relation Between Agriculture & Industry; Technological Changes; Institutional Reforms; Price Policies; Socio-Political Factors; Agricultural Growth Performance; Industrial Policy & Performance; Public & Private Sectors; the Small Sector; Recent Liberalisation Measures; Growth & Productivity in Indian Industry; Role of Policy in Industrial Development; Foreign Trade and Balance of Payments.
Keywords: Economic development